Pendampingan Penyusunan Laporan Keuangan Sederhana pada UMKM Home Industry Donat Lembut Prospero di Kota Lhokseumawe - Almunadiya Almunadiya; Raudhatinur Raudhatinur; Intan Maulida; Rahmiatul Aula; Venna Maulida Mustika (Jurnal Ragam Pengabdian, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the national economy, particularly in creating employment opportunities and improving community welfare. However, many MSMEs still face financial management problems due to limited accounting knowledge and the absence of structured financial records. This condition was also experienced by Home Industry Donat Lembut Prospero in Lhokseumawe City, which had not implemented systematic financial recording. This community service activity aimed to assist the business owner in preparing simple financial reports. The methods consisted of three stages: pre-implementation, implementation, and evaluation. The implementation stage included training and intensive mentoring on transaction recording, cost classification, and profit/loss report preparation. The results showed significant improvements in the partner's understanding and ability to manage business finances. The partner was able to record transactions systematically, separate business and personal finances, and prepare simple profit/loss reports independently. The financial records also revealed that the business had previously experienced substantial undetected losses. Thus, the mentoring activity successfully improved financial management practices in the MSME.